A multicenter DeCOG study on predictors of vemurafenib therapy outcome in melanoma: pretreatment impacts survival - Ugurel, S.; Loquai, C.; Kaehler, K.; Hassel, J.; Berking, C.; Zimmer, L.; Haubitz, I.; Satzger, I.; Mueller-Brenne, T.; Mikhaimer, N. C.; Becker, J. C.; Kilian, K. J.; et al. (Annals of Oncology, 2015)
Kinase inhibitors targeting the BRAF V600 mutation have become standard in the treatment of metastatic melanoma. Albeit in wide clinical use, the patterns associated with therapy outcome are not fully elucidated. The present study was aimed to identify predictive factors of therapy response and survival under the BRAF inhibitor vemurafenib.This multicenter retrospective study analyzed patient, tumor, and pretreatment characteristics collected in BRAF V600-mutated stage IV melanoma patients before single-agent therapy with the BRAF inhibitor vemurafenib.A total of 300 patients from 14 centers were included into this study with a median follow-up time of 13.0 months. Median progression-free survival (PFS) was 5.1 months; median overall survival (OS) was 7.6 months. Best response under vemurafenib was associated with serum lactate dehydrogenase (LDH; <= versus >upper normal limit; P = 0.0000001), Eastern Cooperative Oncology Group (ECOG) overall performance status (OPS) (0 versus >= 1; P = 0.00089), and BRAF mutation subtype (V600E versus V600K; P = 0.016). Multivariate analysis identified ECOG OPS >= 1 [hazard ratio (HR) = 1.88; P = 0.00005], immunotherapy pretreatment (HR = 0.53; P = 0.0067), elevated serum LDH (HR = 1.45; P = 0.012), age >55 years (HR = 0.72; P = 0.019), and chemotherapy pretreatment (HR = 1.39; P = 0.036) as independent predictors of PFS. For OS, elevated serum LDH (HR = 1.99; P = 0.00012), ECOG OPS >= 1 (HR = 1.90; P = 0.00063), age >55 years (HR = 0.65; P = 0.011), kinase inhibitor pretreatment (HR = 1.86; P = 0.014), immunotherapy pretreatment (HR = 0.57; P = 0.025), chemotherapy pretreatment (HR = 2.17; P = 0.039), and male gender (HR = 0.70; 95% confidence interval 0.50-0.98; P = 0.039) were found as predictors.Our data demonstrate that the type of pretreatment strongly influences the outcome of vemurafenib therapy, with a precedent immunotherapy showing a positive, and a prior chemotherapy and kinase inhibitors showing a negative impact on survival, respectively. Moreover, we show that the patient's OPS, serum LDH, age, and gender independently impact vemurafenib therapy outcome. These findings should be taken into account for the future design of therapy sequencing in BRAF V600 mutation-positive melanoma patients.
EVALuna2:19580